IMPROVING LEARNING OUTCOMES IN PANCASILA AND CITIZENSHIP EDUCATION SUBJECTS (PPKN) THROUGH THE SNOWBALL THROWING TYPE LEARNING MODEL FOR STUDENTS AT SMKS YPPK LIMBUNG, GOWA - tapa, Asri; Suhendrik, Suhendrik; Wahid, Surahmi (Unmul Civic Education Journal, 2022)
Learning Pancasila and Education Citizenship (PCE) in students is not just memorizing but also having an understanding of the material presented. One that affects the success of an educational process is student activity. Based on research at SMKS YPKK LIMBUNG, data obtained shows that student learning outcomes are still low because students tend to be passive and do not participate much in learning. The formulation of the problem in this research is whether the use of the snowball throwing type can increase activity, student learning outcomes and the learning process of Civics subjects in class X OTKP at SMKS YPKK Limbung? The purpose of this study was to identify and describe the activities and learning outcomes using the snowball throwing type in PCE Class X OTKP learning at SMKS YPKK Limbung. This research uses Classroom Action Research. The data obtained from qualitative data and quantitative data. Data collection techniques through observation of student activities to determine the increase in student learning activities, tests to determine student learning outcomes and documentation.